Situated Interior - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2023)
The idea of a situated interior reflects the conceptual understanding of an expanded range of interiority from the self to the outside world; it involves traversing rigid boundaries to allow fluidity and continuity. The situated interior considers the critical role of other things in defining the interior practice, from the practice of inhabitation and the practice of making and designing to the dynamic formation of the discipline. The collection of articles in this issue of Interiority demonstrates the numerous ways particular situations define the practice of design, inhabitation, and the discipline of the interior. The narratives of various situations presented in this issue of Interiority demonstrate the relational qualities of self, interior, and context manifested in the continuous process of making, inhabiting, and experiencing. They highlight the critical role of such relational qualities as a foundation for a better understanding of interior practice and interior inhabitation that are dynamic and meaningful.